Determination of the Cardiac Patients Knowledge toward Using Anticoagulant Medications at Missan Governorate Hospitals - khafel, Mohannd; yousif, Haleema (Iraqi National Journal of Nursing Specialties, 2019)
Objective- the study aim to determine the cardiac patient knowledge about anticoagulant medications using and its relationship with demographic data(age. gender. level of education. occupational). Methodology- A descriptive study(quasi-experimental)design was carried out to determine cardiac patient knowledge consider to using anticoagulant medications . Starting from(1th Jun 2017 to5th October 2018).To achieve the objectives of the study, a non-probability sample (a purposive sample) consisted of random sample comprised of (30) patients were taken anticoagulant medications ..The measurement of patient knowledge were collected through the use of questionnaire which is related to patient knowledge toward using the anticoagulant medications. The questionnaire was interview with cardiac patients who were attended coronary care unit at Al-Sadder Teaching Hospital, and Missan Center of Cardiac Disease and in the Medical Consulting after obtaining agreement from the patients throughout using arabic version of questionnaire. The researcher conducted private meeting with each patient who spends about 25-30 minute to respond to the interview which were developed for the purpose of the study. Instrument validity was determined through content validity, by a panel of experts. Reliability of the instrument was determined through the use of Cronbach Alfa which was (0.85) which are strong acceptable for acute myocardial infarction patients’. Analysis of data was performed through the application of descriptive statistics (frequency, percentage) and inferential statistics (t-test and one way analysis of variance) . Result. when we using mean of score the study showed that low level of knowledge for some items and moderate level of knowledge to other items when ( Low 0.0-0.33) (Moderate 0.34-0.76) (0.67-1.0High).and the result study showed no significant differences between cardiac patient knowledge and demographic data (age, gender ,level of education, occupational) . Recommendation-The researchers recommend the implementation of continuous education programs for cardiac patient about using anticoagulant drugs